Study of Medical Waste and Its Management at Wangaya Hospital in Denpasar - Muliarta, I Nengah (International Research Journal of Management, IT & Social Sciences, 2016)
Medical waste has three forms; solid, liquid and gas which derives from hospital activities which contains microorganism, chemical material and radioactive substances. Based on description above, this research was necessary to be conducted to handle the negative impact of medical waste to the environment. The research objectives were 1) in order to know the medical waste management system of Wangaya Hospital in Denpasar, and 2) studying more about medical waste quality of Wangaya Hospital in Denpasar. The research was a case study in using method that was designed by combining the observation data with the laboratory data analyses. The research location was in Denpasar of Wangaya Hospital (B type) regarding on the high occupancy rate of the patient was compared to other hospital (B type) in Bali. The research results was to show that 1) the medical waste management of Wangaya Hospital in Denpasar was suitable yet to meetÂ  the procedure of medical waste from Decree of Minister of health No.1204 in 2004, regarding Health Condition of Environmental Hospital. The laboratory results show that the medical waste quality in Denpasar Wangaya Hospital was above the maximum of standard limit based on Decree of Minister No. 58/MENLH/12/2004. The ashes of incinerated medical waste contained a Hg heavy metal until 2,39 ppm. Based on the research results it was concluded that the management system of medical waste in Denpasar Wangaya Hospital was suitable yet with the procedure, and the medical waste quality of outputs that was released into the environment still exceeding the maximum standard limit. Therefore, it is recommended that Denpasar Wangaya Hospital should undertake the evaluation in management system of the medical waste and its treatment plan to reduce the effluent in its output products in order to comply with the standard limit.